Impact of digital media on emotional, social and moral development of children - Globokar, Roman (Array, 2018)
Digital media is radically changing the way people communicate and influencing the thought processes and experiences of children and adults. New technologies pose a challenge to the educational process. The paper presents the results of the latest research on the impact of digital technology on the emotional, social, and moral development of children. School should respond to the challenges of the digital world by promoting self-respect among children, emotional development, community affiliation, creativity, and innovation. Furthermore, the key to the success of the educational process is the creative passion of the teacher.